Optimising participation of persons with cognitive impairment in a national dementia registry: challenges and solutions. Issue 6 (21st June 2021) - Lin, Xiaoping; Wallis, Kasey; Ahern, Susannah; Brodaty, Henry; Rowe, Christopher; Kain, Barbara; Lambourne, Sally; McNeil, John; Ward, Stephanie A.
Abstract: Clinical quality registries are increasingly utilised to monitor and improve healthcare quality. Opt‐out consent is recommended to maximise participation and ensure validity of data, however, presents specific considerations when including persons with impaired decision‐making abilities. This paper describes the innovative Australian Dementia Network Registry recruitment framework designed to optimise inclusion of people with dementia and mild cognitive impairment.